Ecological Entrepreneurship: Essence, Composition and Specific Features - Mirzaeva Nilufar Sabirjanovna (American Journal of Botany and Bioengineering, 2024)
In this article, the essence of ecological entrepreneurship, which is one of the important forms of social entrepreneurship, scientific-theoretical approaches and types of ecological entrepreneurship are studied. Mechanisms of implementation of ecological entrepreneurship as an integral part of ecological economy are analyzed. Mechanisms for the sustainable development of ecological entrepreneurship have been developed, and the researcher has presented his proposals for solving existing problems.